2022
DOI: 10.1007/s42765-022-00237-5
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Electrospinning as Versatile Supports for Diverse Nanofibers and Their Applications in Environmental Sensing

Abstract: Rapid industrialization is accompanied by the deterioration of the natural environment. The deepening crisis associated with the ecological environment has garnered widespread attention toward strengthening environmental monitoring and protection. Environmental sensors are one of the key technologies for environmental monitoring, ultimately enabling environmental protection. In recent decades, micro/nanomaterials have been widely studied and applied in environmental sensing owing to their unique dimensional pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 253 publications
0
21
0
Order By: Relevance
“…Moreover, the intercalation of MPD monomers into the swollen oleophobic MMT-H + further hinders their diffusion, accounting for the formation of ultrathin and dense laminar PA layers. It is hypothesized that this can be attributed to the delamination of MMT-H + due to the charge effect, swelling and surfactant dispersion during electrospray, followed by the postannealing step. ,, Besides, the extensive surface area provided by the ultrathin delaminated clay nanoplates allows for in situ interfacial polymerization and surface cross-linking before the aerosols make contact with the support membrane. Numerous researchers have provided compelling evidence of the interfacial compatibility of exfoliated nanomaterials at optimal loading in traditionally manufactured polymer nanocomposites, where the polymerization occurs around the 2D nanostructures. Yet, little has been demonstrated on the in situ polymerization during electrospray fabrication.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the intercalation of MPD monomers into the swollen oleophobic MMT-H + further hinders their diffusion, accounting for the formation of ultrathin and dense laminar PA layers. It is hypothesized that this can be attributed to the delamination of MMT-H + due to the charge effect, swelling and surfactant dispersion during electrospray, followed by the postannealing step. ,, Besides, the extensive surface area provided by the ultrathin delaminated clay nanoplates allows for in situ interfacial polymerization and surface cross-linking before the aerosols make contact with the support membrane. Numerous researchers have provided compelling evidence of the interfacial compatibility of exfoliated nanomaterials at optimal loading in traditionally manufactured polymer nanocomposites, where the polymerization occurs around the 2D nanostructures. Yet, little has been demonstrated on the in situ polymerization during electrospray fabrication.…”
Section: Resultsmentioning
confidence: 99%
“…These are crucial factors that influence the inherent permeability and water/ion permselectivity of the membrane. Previous research has unequivocally established that the selection of cosolvents and fabrication techniques are critical strategies for effectively managing the thickness of PA film and the size of the nanopores. In a seminal study, Choi et al (2015) successfully prepared a PA membrane via molecular layer-by-layer assembly utilizing polyelectrolytes, which resulted in a remarkable 98.2% NaCl rejection and 23.0 L m –2 h –1 water flux . Further research in this domain is focused on enhancing water permeance by reducing the thickness to the nanoscale and introducing nanovoids into the sublayers using techniques such as electrospray, nanofoaming, and nanobubbling. , Of these, spray-assisted fabrication has been shown to provide tunable thickness and pore size while ensuring high dispersibility of nanofillers. Nevertheless, the degradation of the PA layer due to chlorination remains the primary factor inhibiting the widespread adoption of this membrane technology in heavily polluted environments, where chlorine cleaning is a necessity. , …”
Section: Introductionmentioning
confidence: 99%
“…Environmental safety is intricately connected to human well-being, and the contamination of the environment and food presents a significant threat to human health. With the rapid development of global industrialization, the discharge of toxic industrial waste gas and wastewater not only leads to serious air, water resources, and soil pollution, but also poses a serious threat to human health along with the food chain . Therefore, a series of detection technologies with excellent performance indicators such as high sensitivity and stability have been developed, including high performance liquid chromatography, gas chromatography, electrochemical techniques, surface-enhanced Raman spectroscopy, fluorometric detection, and colormetric detection.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, developing rapid and sensitive detection methods for these substances, particularly for easy-to-use sensors, is a critical challenge. Notably, electrospun nanofibers demonstrate great potential for the development of novel detection devices, addressing the challenges associated with expensive, complex, and time-consuming traditional detection methods . The multifunctionalized nanofiber-based colorimetric method combines sensitive sensors and electrospinning technology, providing a simple and direct detection method .…”
Section: Introductionmentioning
confidence: 99%
“…To date, it is still a great challenge to develop suitable strategies to optimize the separation rate of carriers and maximize the photocatalytic activity of BiOBr. It has been demonstrated that the size and shape of photocatalysts have an impact on photocatalytic performance. For example, a 2D nanosheet structure with a large specific surface area provides more reaction sites and thus promotes photocatalytic reactions. Among the various shapes of BiOBr, the flower-shaped microsphere structure of BiOBr enriched with nanosheets maximizes its specific surface area while promoting the adsorption of pollutants . In addition, doping rare earth ions into BiOBr is an effective way to enhance the separation efficiency of electron–hole pairs. However, the rapid recombination of photogenerated carriers and the high surface energy of microspheres result in severe aggregation, thus imposing limitations on photocatalytic activity. Assembling microspheres on fibers provides a feasible way to prevent agglomeration and facilitates recycling. …”
Section: Introductionmentioning
confidence: 99%